Implementação de técnica, ferramentas e métodos para promover a excelência da qualidade em uma indústria metalúrgica da Serra Gaúcha - Tomasi, Gilberto (My University, 2021)
As a result of the growing appreciation of customers' needs and as a way of guaranteeing their permanence in the extremely competitive market, management had to treat quality as means for survivability. The company already has a great regard in the market in which it operates, it also has good sales and a good manufacturing organization. However, if some existing quality concepts are added to the existing structure, it will certainly improve even more, reaching the excellence that managers so want. Therefore, with this dissertation, it is intended to show the need to identify existing problems and for each opportunity for improvement to bring a sequence of techniques, tools and methods to promote quality excellence within the organization and thus exceed expectations and also gain new customers. Therefore, the theoretical framework brings some literary alternatives that can add in the efficiency of manufacturing and assembly processes. To improve the results, a work method was created that forms teams to identify problems and, in an organized way, analyze and establish action plans, which, if well planned, can bring very favorable gains. For that, it is necessary to train the leaders, improve the manufacturing and assembly stages and develop indicators to assess the efficiency of the processes, thus establishing a cycle of continuous improvement. With the progress of the actions, it is possible to observe the evolution of quality in all sectors. Comparing data recorded over a period of six months and evaluating the results, an evolution of quality in the manufactured products is perceived. In 2019, 69,576 manufacturing orders were registered, with 1,658 occurrences related to quality. In 2020, 61,317 orders were put into production, with 864 occurrences. Analyzing the two semesters it is possible to identify a decrease of 52.11% in the occurrences in 2020 with only 13.41% less orders. [resumo fornecido pelo autor]
Como consequência da crescente valorização das necessidades dos clientes e como forma de garantir a permanência no mercado que é extremamente competitivo, a gestão da empresa precisou tratar a qualidade como medida de sobrevivência. A empresa já possui um ótimo conceito no mercado em que atua, possui também um bom faturamento e uma boa organização fabril. Entretanto, se for agregado à estrutura existente alguns conceitos de qualidade, certamente vai melhorar ainda mais, podendo chegar na excelência que os gestores tanto querem. Sendo assim, com esta dissertação, pretende-se mostrar a necessidade de identificar os problemas existentes e para cada oportunidade de melhoria trazer uma sequência de técnicas, ferramentas e métodos para promover a excelência da qualidade dentro da organização e, assim, superar as expectativas e também conquistar novos clientes. Para aperfeiçoar os resultados foi estruturado um método de trabalho que cria equipes para identificar os problemas e, de uma forma organizada, analisar e estabelecer planos de ações, que se bem planejados podem trazer ganhos favoráveis. Para tanto, é preciso capacitar as lideranças, melhorar as etapas de fabricação e montagem e desenvolver indicadores para avaliar a eficiência dos processos, estabelecendo, assim, um ciclo de melhoria contínua. Com o andamento das ações foi possível observar evolução da qualidade em todos os setores. Comparando dados registrados em um período de seis meses e avaliando os resultados, percebe-se uma evolução da qualidade nos produtos fabricados. Em 2019 foram registradas 69.576 ordens de fabricação, com 1658 ocorrências relacionadas à qualidade. Em 2020 foram colocadas em fabricação 61.317 ordens, com 864 ocorrências. Analisando os dois semestres é possível identificar uma diminuição de 52,11% nas ocorrências em 2020 com apenas 13,41% a menos de ordens. [resumo fornecido pelo autor]
Keywords: Administração da produção; Controle de qualidade - Indústria; Processos de fabricação; Qualidade dos produtos; Indústrias metalúrgicas; Production management; Quality control - Industry; Manufacturing processes; Quality of products; Metalworking industries